Gender-based violence as a barrier to women rights towards socio- environmental sustainability - A.C. De la Parra-Guerra; J. Truyol-Padilla; C. García-Alzate; F. Fuentes Gandara (Global Journal of Environmental Science and Management)
This study provides an exhaustive analysis of the intersection between gender-based violence and environmental sustainability, focusing on the Colombian experience, particularly within the context of armed conflict and migration. This analysis investigates the emerging area of research in Colombia that focuses on preventing gender-based violence from ecological and environmental viewpoints. Adopting a socio-ecological lens, this study highlights the ways in which women are disproportionately affected by gender-based violence and environmental challenges, particularly in contexts defined by conflict, displacement, poverty, and inadequate access to resources. Women in these contexts face direct violence and the compounded hardships associated with losing essential natural resources that sustain their families and communities. The review highlights addressing these intertwined challenges by empowering women as agents of socio-environmental transformation. It emphasizes the need for holistic interventions linking gender-based violence prevention with strategies for environmental protection, including initiatives tailored to local contexts. These interventions involve environmental education programs, the promotion of female leadership in conservation efforts, and the implementation of community-based projects driven by women, fostering their role as key drivers of sustainable change. Moreover, the research emphasizes the multifaceted consequences of armed conflict on Colombia''s social and environmental systems, which further amplify the vulnerabilities of women and contribute to increased ecological decline. Addressing these issues jointly, it calls for public policies and programs adopting integrated socio-ecological perspectives to tackle gender-based violence and promote environmental sustainability. The proposed approach equips women with tools to combat violence and strengthens their capacity to contribute to environmental conservation and the establishment of resilient communities. This study advocates for a framework bridging gender-based violence prevention and environmental protection as a pathway to achieving inclusive, participatory, and sustainable peace. This strategy presents a viable structure for fostering enduring social and environmental improvements. Such an approach is particularly relevant for Colombia, where the legacy of conflict and displacement continues to pose significant challenges to both gender equality and ecological integrity.